2015
DOI: 10.1590/0102-311x00009914
|View full text |Cite
|
Sign up to set email alerts
|

Trends in child labor and the impact on health in adulthood in Brazil from 1998 to 2008

Abstract: There is little evidence in Brazil on the impact of child labor on health status in adulthood. This study aimed to investigate trends in child labor in Brazil and estimate the long-term effects of child labor on the health of Brazilian adults, using nationally representative databases (Brazilian National Household Sample Survey) from three different years (1998, 2003, and 2008). The models were based on a two-stage linear equation and Generalized Method of Moments (GMM). The results suggest that child labor ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(44 reference statements)
0
2
0
4
Order By: Relevance
“…O trabalho infantil, independentemente da atividade, teve influência negativa em indicadores de saúde de adultos, direta (impacto em saúde) e indiretamente (perda de anos de estudos). Assim, o trabalho infantil impõe um prejuízo em longo prazo à população no Brasil, influenciando adversamente a formação de capital humano via impactos negativos em saúde na fase adulta (33) .…”
Section: Página112unclassified
“…O trabalho infantil, independentemente da atividade, teve influência negativa em indicadores de saúde de adultos, direta (impacto em saúde) e indiretamente (perda de anos de estudos). Assim, o trabalho infantil impõe um prejuízo em longo prazo à população no Brasil, influenciando adversamente a formação de capital humano via impactos negativos em saúde na fase adulta (33) .…”
Section: Página112unclassified
“…Ao abordar o trabalho de crianças e adolescentes, estudos apontaram as perdas de momentos de vida, com alijamento do direito e acesso à educação, menor tempo para estudo e qualificação profissional (Thomé et al, 2010), tendo como consequência piores níveis de saúde (Dall'Agnol et al, 2015;Kassouf et al, 2001;Nishijima et al, 2015), perdas subjetivas pelo comprometimento de momentos importantes para o desenvolvimento, redução da autoestima e autorrealização (Costa et al, 2015) e menor remuneração na fase adulta (Monte, 2008;Souza & Pontili, 2007).…”
Section: Vivências De Trabalho E Os Significados Atribuídos a Eleunclassified
“…8 Ideas for future work on child labour Evidence from the literature, including studies such as Nishijima, Souza and Sarti (2015) and Nicolella and Kassouf (2018), has shown the effects of engaging in child work on health outcomes. These studies have shown that early labour market entry is associated with poor physical health in adulthood.…”
Section: Re-examining Child Labour Through a New Lensmentioning
confidence: 99%